PENERAPAN KOLABORASI STRATEGI METAKOGNITIF DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MENULIS KARYA ILMIAH - Bayu Dwi Nurwicaksono (Universitas Nahdatul Ulama Surabaya, 2017)
This research is motivated by the low accumulation of cognitive, affective, and psychomotor values of students in scientific writing, that’s 63.45. Whereas based on preliminary tests, students have potential in intellectual development. The purpose of this study is to describe student learning outcomes on the materials of writing scientific papers by applying metacognitive strategy collaboration. This classroom action research is a quantitative descriptive study. The subject of his research is the students of class XI.IPA.2 SMA Trisila Surabaya. The instruments used are tests and not test. The result of the research showed that the students’ learning achievement significantly improved from the average score of the students on the first cycle which reached 72.97 with the total number of students who have completed the study as much as 82.05% to the final grade of the students on cycle 2 reaching 87.07 with the number of students have completed learning 100%. Therefore, this metacognitive collaboration strategy is suggested to be used in the learning of writing scientific papers.